Pengembangan Handout Biologi Berbentuk Katalog Disertai Gambar Berwarna pada Materi Sistem Pernapasan - Zuli Nofiyanti; Supiana Dian Nurtjahyani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
Teaching materials tailored to the student's condition will make it easier for students to understand the material delivered and provide a memorable experience. It is therefore necessary to develop a Biology handout in the form of a catalog with color images on the Respiratory Material Material of quality in terms of validity, effectiveness and practicality. The development of this handout is displayed in the form of a catalog and is complemented by color images with the aim of motivating students to learn and make it easier to understand the material with the help of color images. The development model used is the ADDIE model. Data collection techniques use validation sheet instrument, observation sheet, test sheet and questionnaire. The results showed that Biology handouts in the form of catalogs with color images on the respiratory system material were declared valid, practical and effective and suitable for use as a learning medium for students.